THE EFFECT OF GIVING KATE MAS LEAF EXTRACT (Euphorbia heterophylla L.) AS LAXATIVE ON MICE (Mus musculus) - Hafid, Muliana; Firmansyah, Firmansyah; Waris, Muhammad Anugerah Alam (Jurnal Jamu Kusuma, 2025)
Kate Mas plant (Euphorbia heterophylla) is a weed plant that grows in humid areas. Traditionally kate mas leaves are used to treat constipation, bronchitis, anti-inflammatory and asthma. The purpose of this study was to determine the effect of giving kate mas leaf extract (Euphorbia heterophylla) as a laxative to mice (Mus musculus). The research design was experimental at the Pharmacology Laboratory, Faculty of Mathematics and Natural Sciences, Pancasakti University. This study used 15 mice which were divided into 5 groups which had been fasted 1 hour before treatment, using loperamide HCl suspension as inducer. The first group was given CMC Na suspension as a negative control, the second group was given dulcolactol syrup as a positive control, groups three, four and five as the treatment group were given katemas leaf ethanol extract with doses of 70 mg/20 g BW, 140 mg/20 g BW and 280 g respectively. mg/20g BW. Data were analyzed using the SPSS application, the Kruskall-Wallis Test followed by testing using the Mann-Whitney Test method to see differences between treatment groups. The results showed that kate mas leaf extract had a laxative effect on mice. The first dose treatment group, namely 70 mg/20 g BW, had the same laxative effect as the positive control group with a significance value (P> 0.05) from these results it could be concluded that kate mas leaf extract had a laxative effect on mice, the most effective treatment group was group three with a dose of 70 mg/20 g BW.